Organocatalytic asymmetric Michael addition of unprotected 3-substituted oxindoles to 1,4-naphthoquinone - Yu, Jin-Sheng; Zhou, Feng; Liu, Yun-Lin; Zhou, Jian (Beilstein Journal of Organic Chemistry, 2012)
We reported the first example of organocatalytic Michael addition of unprotected 3-prochiral oxindoles 1 to 1,4-naphthoquinone. Quinidine derivative (DHQD)2PYR was found to be able to catalyze this reaction in up to 83% ee, with moderate to excellent yields. This method could be used for the synthesis of enantioenriched 3,3-diaryloxindoles, and the catalytic synthesis of which was unprecedented.
Keywords: 3,3-disubstituted oxindoles; Michael addition; organocatalysis; quaternary stereogenic center; unprotected 3-substituted oxindoles